Application of Giving Question and Getting Answer Learning Model to Student Learning Outcomes at Class VII Christian Religious Education Lessons of SMP Pembangunan Galang - Tami Sitanggang; Bangun Munthe; Imelda Butarbutar (International Journal on Advanced Science, Education, and Religion, 2024)
The purpose of this research is to see how the Giving Question and Getting Answer Learning Model is applied to student learning outcomes in Class VII Christian Religious Education Lessons at Pembangunan Galang Middle School. This type of research is classroom action research with the research population being all class VII students at Galang Development Middle School. Where in this research used cycle I and cycle II. Based on the results of research and observations carried out by researchers, it can be concluded that the application of the GQGA learning model in improving student learning outcomes in class VII religion lessons at SMP Pembangunan Galang is said to be successful. The results of the research stated that the application of the GQGA learning model showed an increase in student activity from the learning outcome value data in cycle I. The number of students who completed their studies was 11 people (45.8%) while in cycle II the number of students who completed their studies was 19 students (88 .33%) increased learning outcomes from cycles I and II by 41.6%. Keywords: Learning Model, Giving Questions and Getting Answers, Student Learning Outcomes